(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Youths are precious human resources of every country. An unhealthy lifestyle among youth is a serious and often unnoticed problem which can lead to various Noncommunicable diseases. This study was done in a rural area of Bihar with the objective to assess their lifestyle using Simple Lifestyle Indicator Questionnaire (SLIQ). Materials and Methods: A cross sectional study done in a rural nursing college of Bihar. A validated SLIQ was used to assess the lifestyle which included dietary consumption, physical activity, and self perceived stress, tobacco and alcohol consumption. Life style was assessed by calculating SLIQ score. Results: Study included 151 rural students with a male female ratio of 0.78:1 and age group ranging from 18-31 years. 53.7% consumed green leafy salad more than six times per week and 67.5% had fresh fruits less than three times per week although 66.9% ate high fibre cereals twice or more times per day. Light, moderate and strenuous exercise was preferred by 71.6%, 33.8% and 16.5% respectively. Alcohol abuse was observed in 15.2% while 13.9% consumed tobacco. Self perceived stress scoring showed stressful lifestyle among 27.1% of students. Mean SLIQ score was 5.31 (SD=2.37). Discussion: Rural students consumed more of green leafy salad and high fibre cereals as compared to fresh fruit intake. Most of them were engaged in light exercise. Substance abuse like alcohol and tobacco was almost similar. About one fourth students showed stressful lifestyle. Lifestyle and health promotion policies are required for youth to decrease NCDs. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.401-406